Thyroid dysfunction and hepatic steatosis in overweight children and adolescents. Issue 1 (14th February 2016) - Kaltenbach, T. E.‐M.; Graeter, T.; Oeztuerk, S.; Holzner, D.; Kratzer, W.; Wabitsch, M.; Denzer, C.
Summary: Background: Overt or subclinical hypothyroidism is a common finding in adult populations affected by non‐alcoholic fatty liver disease (NAFLD). Currently, there are only sparse data available on the association of thyroid dysfunction and NAFLD in obese children and adolescents. Objective: The study aims to investigate the association of thyroid function test values with NAFLD and metabolic risk factors in a population of obese children and adolescents. Methods: A total of 332 overweight and obese children and adolescents (170 girls) aged between 10 and 19 years were analysed. Subjects underwent ultrasound examination of the liver. Thyroid function was evaluated by laboratory determination of thyroid‐stimulating hormone (TSH), total triiodothyronine (T3) and total thyroxine levels. All included subjects were either euthyroid or had subclinical hypothyroidism (TSH > 4 μU mL −1, normal thyroxine). Further metabolic profiling included the determination of lipid status, insulin and liver function tests. Anthropometric parameters body mass index, waist and hip circumference were documented. Results: The prevalence of hepatic steatosis was 29.8%. Subjects with NAFLD had significantly higher TSH levels than those without ( p  = 0.0007). After dividing TSH values into quartiles, both univariate and multivariate analyses (adjusted for age, body mass index–standard deviation scores and stage of puberty) showed a significant association with hepatic steatosis ( p  < 0.05). Conclusion: Taking possible variables into consideration, our results show that there is a significant association between hepatic steatosis and the TSH levels in obese children and adolescents. Mild thyroid dysfunction may therefore have a role in determining an unfavourable metabolic profile in obese children and adolescents.